AB0447 Antimalarials improve survival of systemic lupus erythematosus on cholesterol: results of a fifteen-year chinese multicenter retrospective study in jiangsu province. (15th June 2017) - Wang, F; Zhang, W; Wang, S; Pan, W; Liu, L; Wu, M; Ding, X; Wei, H; Zou, Y; Feng, X; Sun, L
Abstract : Background: Nowadays the importance of antimalarials, especially hydroxychloroquine (HCQ) and chloroquine (CQ), in treatment of systemic lupus erythematosus (SLE) has been demonstrated. However, few have examined the efficacy of HCQ and CQ on eastern Chinese SLE patients. Methods: The analysis is based on 1372 patients who were enrolled in a retrospective study of 26 centers from January 1st, 1999 through December 31st, 2009, during which time is their first hospitalization. Baseline and follow-up clinical, laboratory and therapeutic data and survival status before April 30th, 2015 were recorded. Statistical analysis consist of Chi-square test, t -test, Kaplan-Meier curves and logrank test. Results: Compared with 562 patients without HCQ or CQ treatment, the hazard ratio (HR) of deaths in 810 patients taking those was reduced (HR 0.52, 95% CI 0.38–0.70, p<0.001). 376 of these 1372 patients experienced their second hospitalization, during which treating group (165 of 376) showed lower blood level of total cholesterol (TG), compared to control group (4.47 (0.13) vs 5.03 (0.21), p=0.027), while no statistical difference of TG exists between the two groups' first hospitalization (p>0.05). Other metabolic data, such as systolic and diastolic blood pressure, fasting blood sugar, Triglyceride and uric acid were similar between the two groups in two times of hospitalization. On second inpatient visit, disease activity (SLEDAI, blood sedimentation rate, complement) and organ involvements (SLICC) of those who took antimalarials and no users have no significant differences. Conclusions: Use of HCQ or CQ lower the risk of mortality and TG levels of eastern Chinese SLE patients. Disclosure of Interest: None declared